The essence and content of administrative and legal (organisational and legal) principles of activity in a particular area in Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2025)
This study analyses the understanding of the content and essence of the principles as a legally significant term. The validity of the study is due to the fact that in the scientific and legislative spheres the term “principles” is systematically used with different content. The article analyses the topics of dissertation research on legal issues which were submitted for consideration to the Academy of Legal Sciences of Ukraine.The normative essence of the term “principles” is briefly characterised, which made it possible to identify its main characteristics. It is noted that in legislation the term “principles” refers to the foundations, principles, grounds, procedure and legal regime of activity, the list and general powers of the entities which carry it out, key procedures for its implementation, strategy, purpose, tasks, directions, and specific features of the formation and implementation of state policy in the relevant area.The conclusions regarding the content of the term “principles” are made on the basis of the opinions of other scholars. The comparative analysis of the types of principles is carried out, in particular, legal, organisational and administrative principles. The article emphasizes that all these categories are interrelated, and the latter two may be generally identified in the context of the rule-of-law State, except for the cases when the scope of research is directly defined by administrative and tort law.It is determined that the principles are a set of ideas, principles, qualities, directions, goals and foundations that serve as the basis for any type of activity. At the same time, however, the principles may be used in phrases as a mechanism or a way of carrying out an activity.The article proposes to identify administrative and legal principles and organisational and legal principles, which are understood as a set of rules of conduct of subjects of a certain activity or any relations, methods and mechanisms for organising their activities, peculiarities of their legal status in the system of public administration and public relations, as well as principles, ideas of functioning and directions of their improvement which are “pointers” for their development and ensuring.